Student perceptions on their transition experiences at a South African university offering a first-year experience programme. (Journal of Student Affairs in Africa, 2022)
The transition from high school to university is often a challenge for many students, as they face numerous academic and social adjustments during this time.  For the 2020 cohort, these challenges were compounded by the COVID-19 pandemic, which further exacerbated the existing concerns and uncertainties.  This study reports on the perceptions of a cohort of first-year students enrolled in 2020 at the onset of the COVID-19 pandemic regarding their transition experiences. The analysis was carried out against the backdrop of a pilot first-year experience programme at one South African university.   Data was collected using a survey method from a sample of 299 students who had participated in the pilot programme.  A multi-construct approach was used to assess student perceptions on the success of the First Year Experience programme in providing i) a supportive learning environment, ii) assisting students to understand academic demands, and iii) creating stimulating learning experiences with acceptable levels of reliability (0.66-0.74).   Despite facing many transitional challenges at the beginning of the academic year, student responses to questions on the above three factors were affirmative.  This suggested that students perceived their experiences of support and interactions within the university as instrumental in assisting them to cope with transitional challenges.  These findings provided the necessary guidance for the continuation and improvement of the support given to first-year students.
Keywords: First-Year Experience; transition; student integration